2010
DOI: 10.1159/000284582
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for Hereditary Breast and Ovarian Cancer Information among Mexican, Cuban and Puerto Rican Women at Risk

Abstract: Background: Little is known about the preferences of at-risk Hispanic women to gain information on hereditary breast and ovarian cancer (HBOC). Aims: This study sought to qualitatively explore preferences for HBOC information among at-risk Mexican, Puerto Rican and Cuban women and to pilot a mock brochure aimed at Hispanic women. Methods: Hispanic women aged 18–65 years with a personal or family history of breast or ovarian cancer participated in a semistructured interview. Data were analyzed using a combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 60 publications
(43 reference statements)
0
19
0
Order By: Relevance
“…Through an NCI-funded cooperative agreement, the PSM-MCC Partnership is a collaboration between a minority-serving institution (PSM) and an NCI-designated comprehensive cancer center (MCC) to address cancer-related health disparities among Hispanics. The Tampa-based team of the MCC had an existing study to identify differences in knowledge and attitudes toward HBOC and GT in a multiethnic sample of Hispanic women in Tampa (Quinn et al 2011;Vadaparampil et al 2010a, b). The Puerto Ricobased team of the PSM is conducting a study aimed at identifying the prevalent BRCA mutations in Puerto Rico and at evaluating available models of carrier risk assessment in this population.…”
Section: Overall Study Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Through an NCI-funded cooperative agreement, the PSM-MCC Partnership is a collaboration between a minority-serving institution (PSM) and an NCI-designated comprehensive cancer center (MCC) to address cancer-related health disparities among Hispanics. The Tampa-based team of the MCC had an existing study to identify differences in knowledge and attitudes toward HBOC and GT in a multiethnic sample of Hispanic women in Tampa (Quinn et al 2011;Vadaparampil et al 2010a, b). The Puerto Ricobased team of the PSM is conducting a study aimed at identifying the prevalent BRCA mutations in Puerto Rico and at evaluating available models of carrier risk assessment in this population.…”
Section: Overall Study Contextmentioning
confidence: 99%
“…The Puerto Ricobased team of the PSM is conducting a study aimed at identifying the prevalent BRCA mutations in Puerto Rico and at evaluating available models of carrier risk assessment in this population. Based on these mutual interests, a sample of women were recruited from Puerto Rico and compared with the subsample of Puerto Rican participants from the multiethnic study of Hispanics in Tampa (Quinn et al 2011;Vadaparampil et al 2010a, b). The information collected in this project was intended to inform future population-based studies to better define the prevalence and penetrance of BRCA mutations specific to Puerto Rico.…”
Section: Overall Study Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Research by Quinn et al (2011) found that a majority of Latino women preferred to receive health information where it was discussed in a charla. Being that sexual education and family planning are taboo topics in Honduras, especially among rural areas, the charla provided a setting where both men and women can learn about sexual disease prevention in a medical context.…”
Section: Utilizing Charlas To Address Public Health Issues In Low-litmentioning
confidence: 99%
“…Lack of information on health behaviors and risk perception may be due to low participation rates among Hispanic women in cancer-related research (Underwood 2000). Furthermore, because participation rates have been low among Hispanics as a whole, the efficacy of some cancer-related treatments has not been ascertained within this group, and there are some pharmaceutical studies suggesting racial and ethnic differences in tolerance and efficacy with medications (Tejeda et al 1996;Lahn & Ebenstein 2009;Phan et al 2009). …”
Section: Introductionmentioning
confidence: 99%